Extraordinary simultaneous enhancement of the coercivity and remanence of dual alloy HRE‐free Nd‐Fe‐B sintered magnets by post‐sinter annealing. (20th April 2022) - Huang, Qingfang; Jiang, Qingzheng; Hu, Jifan; Rehman, Sajjad Ur; Fu, Gang; Quan, Qichen; Huang, Jixiang; Xu, Deqin; Chen, Dakun; Zhong, Zhenchen
Highlights: Both the remanence and coercivity are improved after the 2nd annealing process. The coercivity is hugely increased from 10.09 kOe for the as-sintered sample to 17.19 kOe for the 2nd annealed magnet, with a significant increment of 70.37%. The matrix grains are enveloped by a (Pr, Nd, Cu, Ga)-enriched layer after the 2nd annealing process. HRE-free Nd-Fe-B sintered magnets with excellent comprehensive magnetic properties were manufactured by Pr-Fe-Ga boundary addition. Abstract: Post-sinter annealing process plays an important role in the microstructures and magnetic properties of the Nd-Fe-B sintered magnets. In this paper, systematically investigated are the magnetic properties and microstructures of the as-sintered and post-sinter annealed Nd-Fe-B magnets with Pr-Fe-Ga boundary addition. Two choice consecutive annealing methods are adopted at high and low temperatures, namely the 1 st annealing at 880 ºC for 2 h and then the 2 nd annealing at 440 ºC for 3 h. It is exceptional to find out that both the remanence and coercivity are improved after 2 nd annealing process for this type of magnet. The coercivity is hugely increased from 10.09 kOe for the as-sintered sample to 17.19 kOe for the 2 nd annealed magnet, with a significant increment of 70.37% in coercivity. The extraordinary magnetic properties of B r =14.44 kGs, H cj =17.19 kOe and ( BH )max =51.08 MGOe are obtained for the designated Nd-Fe-B sintered magnets without heavy rare earth (HRE) elements manufactured by dual alloy method. The Curie temperature is monotonically decreased from 634 K to 602 K while the c -axis alignment degree is optimized after annealing. Microstructural observation and analysis indicate that the elemental distribution patterns are altered after the 2 nd annealing. The diffusion of the aggregate (Pr, Nd, Cu, Ga)-rich phase from triple junctions into the grain boundary regions is ascribed to the formation of thin and continuous grain boundary layer, which is critical to improve the microstructures and magnetic properties. Graphical abstract: Image, graphical abstract